(untitled) (Journal of Architectural Design, 2023)
Performance dips are perennial contemporaries of construction projects delivery across the globe. Varying degrees of these failures are increasingly attributed to planningrelated problems. While expansive narrations of planning practices are obtainable notably in construction project management literature, the facets of barriers and drivers of effective construction contract planning as precursor of successful project delivery are limitedly accounted. In this study, we examined the barriers inhibiting effective contract planning among contractors in Akwa Ibom State. Survey data obtained from a purposive sample of 50contract planning experts including quantity surveyors, contract managers and engineers designated as contract and project managers in building and civil engineering projects in Uyo were analysed using Mean Item Score (MIS), Friedmans test and Kendall’s Concordance Index (KCI). The results showed that project characteristics, low adoption of technology, pressure management and lack of time and lack of collaboration as well as the dearth of personnel are critical drivers of inefficiencies in contract planning among contractors in the research environment. Across contracting organization structures (size), the test of variation in the perception of planning experts about the critical barriers to effective contract planning does vary significantly. The implication suggests that contracting firm structure could predict the level of planning as well as the effectiveness of contract planning efforts. Amidst this emerging viewpoint, the study concludes that ineffective contract planning are correlates of project characteristics, low adoption of technology, pressure management and lack of time and lack of collaboration. In order to improve the effectiveness of contract planning, the study recommends engagement with state-of-the-art planning applications, education and training and proper timing of pre-construction activities.